1996
DOI: 10.1093/nar/24.5.850
|View full text |Cite
|
Sign up to set email alerts
|

Diastereomeric Specificity of 2',3'-Cyclic Nucleotide 3-Phosphodiesterase

Abstract: The diastereomers of adenosine and uridine 2',3'-cyclic phosphorothioates were tested as substrates for 2',3'-cyclic nucleotide 3'-phosphodiesterase from bovine brain. The enzyme cleaves the Sp (or exo) diastereomers efficiently, whereas the Rp (or endo) diastereomers are resistant to hydrolysis, even after long incubation. As the enzyme exhibits strong substrate inhibition the precise determination of kinetic parameters posed problems, particularly with phosphorothioates. The stereoselectivity of this enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…The cyclic nucleotides were found to be effective in the low micromolar concentration range. The effects of 2Ј,3Ј-cAMP on PT development were observed even at 0.5 M, and maximal efficiency was seen at 5 M. 2Ј,3Ј-Cyclic NADP is also a substrate for 2Ј,3Ј-cyclic nucleotide 3Ј-phosphohydrolase (20). 2Ј,3Ј-cNADP was able to shorten the lag phase before Ca 2ϩ efflux and to increase the rate of Ca 2ϩ release from both kinds of mitochondria, rat brain and liver mitochondria, when they were loaded with threshold Ca 2ϩ concentrations.…”
Section: Discussionmentioning
confidence: 94%
“…The cyclic nucleotides were found to be effective in the low micromolar concentration range. The effects of 2Ј,3Ј-cAMP on PT development were observed even at 0.5 M, and maximal efficiency was seen at 5 M. 2Ј,3Ј-Cyclic NADP is also a substrate for 2Ј,3Ј-cyclic nucleotide 3Ј-phosphohydrolase (20). 2Ј,3Ј-cNADP was able to shorten the lag phase before Ca 2ϩ efflux and to increase the rate of Ca 2ϩ release from both kinds of mitochondria, rat brain and liver mitochondria, when they were loaded with threshold Ca 2ϩ concentrations.…”
Section: Discussionmentioning
confidence: 94%
“…Prior to that, CNPase had already been shown to have substrate stereoselectivity, using nucleoside 2′,3′-cyclic monophosphorothioate analogs [65] .…”
Section: Activitymentioning
confidence: 99%
“…In these analogues, one of the cyclic phosphate oxygen atoms is replaced by a sulfur. Previously, it has been shown that the Sp epimer of 2',3'-cAMPS is a functional substrate for CNPase, while the Rp epimer is not 36 . We used both wild-type CNPase and selected mutants to determine crystal structures of CNPase in the presence of the two phosphorothioate epimers.…”
Section: Phosphorothioate Complexesmentioning
confidence: 99%
“…CNPase has stereospecificity towards 2',3'-cAMPS analogues, with only the Sp epimer being a good substrate 36 . Our crystal structures with both the Sp and Rp epimers indicate subtle differences in the cyclic ligand conformation; while the Sp epimer is very similar to 2',3'-cAMP, the Rp epimer complex structure is missing the nucleophilic water molecule.…”
Section: Further Insights From Active-site Ligand Complexesmentioning
confidence: 99%